Psychocardiology - forgotten science in the service of cardiovascular disease prophylaxis - Jankowska, Paula; Jankowski, Krzysztof; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
Psychocardiology is a science that combines an insight of biomedicine, psychology and sociology sciences. The goal of this discipline is to study the relationship between psychological profile, personality, social functioning and cardiovascular diseases (CVD). Low socio-economic status, deficiency of social support, stress in work environment and in family life, depression, anxiety as well as hostility are partly responsible for risk of developing CVD and a poor prognosis of CVD. In everyday practice of physician clinical interview should be used to identify these psychosocial risk factors. After identification of psychosocial problems multimodal behavioural interventions are recommended to implement in treatment process. They should involve health education, physical activity, psychological and pharmacological therapy and learning of techniques of coping with illness and unfavorable social circumstances. Psychosocial risk factors of cardiovascular diseases are not widely recognized as a cardiovascular risk factor in their own right. However, they contribute to deterioration of treatment adherence and annihilate attempts of lifestyle improving. The pronounced psychosocial aspects of cardiovascular diseases pathogenesis make health promotion in patients and whole population difficult. Thus, considered factors are ponderous public health problem.